2024
DOI: 10.1002/mrm.29998
|View full text |Cite
|
Sign up to set email alerts
|

Myelin bilayer mapping in the human brain in vivo

Emily Louise Baadsvik,
Markus Weiger,
Romain Froidevaux
et al.

Abstract: PurposeTo quantitatively map the myelin lipid‐protein bilayer in the live human brain.MethodsThis goal was pursued by integrating a multi‐TE acquisition approach targeting ultrashort T2 signals with voxel‐wise fitting to a three‐component signal model. Imaging was performed at 3 T in two healthy volunteers using high‐performance RF and gradient hardware and the HYFI sequence. The design of a suitable imaging protocol faced substantial constraints concerning SNR, imaging volume, scan time, and RF power depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…These have reported T 2min values of 0.01-0.1 ms in WM tissue samples 20,42,43 and also used these values to fit in vivo relaxometry data. 44 These studies concluded that a component with T 2min of 5.5 𝜇s and chemical shift of 1.1 ppm corresponds to the myelin bilayer, while a component with T 2min of 100 𝜇s and chemical shift of 2.1 ppm corresponds to other non-aqueous protons such as cell membranes and proteins. Imaging results were enabled by ZTE sequences and dedicated hardware including high-performance gradients and fast transmit/receive switches, while our data was acquired on conventional hardware which limits comparisons that can be made.…”
Section: Discussionmentioning
confidence: 99%
“…These have reported T 2min values of 0.01-0.1 ms in WM tissue samples 20,42,43 and also used these values to fit in vivo relaxometry data. 44 These studies concluded that a component with T 2min of 5.5 𝜇s and chemical shift of 1.1 ppm corresponds to the myelin bilayer, while a component with T 2min of 100 𝜇s and chemical shift of 2.1 ppm corresponds to other non-aqueous protons such as cell membranes and proteins. Imaging results were enabled by ZTE sequences and dedicated hardware including high-performance gradients and fast transmit/receive switches, while our data was acquired on conventional hardware which limits comparisons that can be made.…”
Section: Discussionmentioning
confidence: 99%